Cariprazine's Potential in Improving Social Dysfunction in Patients With Schizophrenia: A Perspective - Morozov, Petr; Bekker, Roman; Bykov, Youri (Frontiers in Psychiatry, 2022)
Social dysfunction is one of the most debilitating aspects of schizophrenia. Treatment of this complex phenomenon, constituted by negative, cognitive, and affective symptoms, has been difficult with the available pharmacological agents, hence it represents an unmet medical need. Cariprazine, a novel, third-generation antipsychotic with a unique mechanism of action has been proven to sufficiently alleviate negative, cognitive, and affective symptoms of schizophrenia. These characteristics make this compound a valid candidate for addressing social dysfunction too. In this perspective, we argue that cariprazine can be viewed as a “socializing drug” that has the ability to improve the patient's functionality and ultimately their quality of life. Data from animal research, clinical trials, an observational study, and patient cases are provided.